Incorporating vegetal fibers for sustainable sandy soil - Adda Berkane, Hachemi; Della, Noureddine; Denine, Sidali; Missoum Benziane, Mahdi (Revista de la Construcción. Journal of Construction, 2023)
Incorporating fibers into the soil is a reinforcement remediation technique to improve its physical and mechanical properties. Depending on the type of fibers, synthetic fibers, have negative impacts on the environment linked to the waste of their chemical industry. Currently, vegetal fibers consider an economic and ecological alternative to soil reinforcement. Therefore, this study aims to evaluate the influence of two types of randomly distributed fibers (Alfa and Sisal fibers) on the mechanical properties of sandy soil. Direct shear tests were performed on Chlef sand at relative density (Dr = 75% and 40%) and of fiber contents varying from 1, 2, 3 and 4% for sand samples reinforced with Alfa fibers and 0.1, 0.3, 0.5 and 0.7% for sand samples reinforced with Sisal fibers. The test results show that the inclusion of vegetal fibers in sandy soil improves the peak and residual shear strength. In addition, soil resistance was found to attain a maximum with the optimums of 0.7% for sisal fiber content and 3% for Alfa fibers.